Application of continuous manufacturing for solid oral dosage forms - Jung, Eun A.; Park, Young Joon; Kim, Joo Eun (Journal of Pharmaceutical Investigation, 2023)
Background: Continuous manufacturing, a new process that applies the concept of time rather than batch size, is gradually being implemented throughout the pharmaceutical industry. In this process, critical quality attribute (CQA) management strategy for pharmaceutical manufacturing must be established through real-time monitoring technology. Therefore, transitioning from existing offline testing to real-time process analysis techniques (PAT; at-line, on-line, in-line) is essential for ensuring the quality of the intermediate and final products. Additionally, exploring the suitability of PAT must also be considered. Area covered: In this review, we discuss the application of real-time monitoring technology in the manufacturing process of solid oral dosage forms. We list each manufacturing process for the solid oral dosage form and select each key unit process to be considered when converting to continuous manufacturing while identifying the CQA. We also comprehensively review the real-time monitoring PAT of the continuous manufacturing process studied to the identified CQA. Therefore, this review goal is understanding the status of monitoring enabling quality control and assurance through the listing of real-time PAT that can control CQA in continuous manufacturing. Expert opinion: In existing studies, there are many individual mentions of real-time monitoring techniques to continuous manufacturing. However, there are relatively few systematic and comprehensive discussions on PAT that can be applied to continuous manufacturing throughout the entire manufacturing process of solid oral dosage forms. Therefore, this review attempts to systematically arrange the real-time monitoring technology applicable to the continuous manufacturing of solid oral dosage forms and lists various examples other than process controls for continuous manufacturing of the drug products listed in ICH guideline Q13. It is hoped that this review will help expand the application of continuous manufacturing in the pharmaceutical industry.
Keywords: Continuous manufacturing; Continuous process; Critical quality attribute; Process analytical technology; Quality by design; Solid oral dosage form